Dental status and measures of deprivation in Clermont- Ferrand, France - Enjary C, Tubert-Jeannin S, Manevy R, Roger-Leroi V, Riordan PJ. (Blackwell Synergy, 2006)
Many background variables, such as socioeconomic status (SES), may be measured at the level of the individual or using some ecological indicators.